Aberrant Breast in a Rare Site: A Case Report - Levent Yeniay; Kilongo Mulailwa; Elmir Asgerov; Cüneyt Hoşcoşkun; Osman Zekioğlu (Case Reports in Medicine)
Aberrant breast tissue is an anomaly in the embryogenesis of the breast that is found along the mammary ridge or out of that line. We report a case of a 71-year-old female patient with an abdominal aberrant breast tissue found incidentally in a piece of mesenteric biopsy. The histological features were consistent with breast tissue.